018. Supraclavicular Flap and Reconstruction With Radial Forearm Flap In Basal Cell Carcinoma Of The Buccal Region: A Rare Case Report - Hamzah, Birgitta Stella Dewi; Riasa, Nyoman Putu (JBN (Jurnal Bedah Nasional); Vol 8 No 2 (2024): Proceeding The 2nd National Conference of Indonesia Surgical EducationDO - 10.24843/JBN.2024.v08.is02.p018, 2024)
Background : Basal cell carcinoma (BCC) progression can invade surrounding tissues, causing local destruction and disfigurement. About 85-90% cases of BCC occur on the head, greatly affecting facial appearance of patients. Functional or cosmetic concerns require skin flap or graft. Case : A patient presented with a wound on his left cheek for 8 years, bleeds easily and painful. There is a muscle-based ulcer, penetrating the oral cavity and a post-biopsy wound is covered with granulation tissue. Laboratory examination showed moderate anemia and chest x-ray did not show any metastases. A supraclavicular flap and intraoral and supraclavicular insertion and intraoral and supraclavicular insertion were performed. In addition, harvesting of the radial forearm flap and partial palmaris longus tendon was conducted. Conclusion: Reconstruction of facial defects in different facial esthetic units is essential following excision of BCC. But it is necessary to plan the stages of reconstruction when more than one facial region is involved. Surgeon skills, patient’s preference, defect size and location are important determinants of esthetic outcomes